Cross-Presenting XCR1+ Dendritic Cells as Targets for Cancer Immunotherapy - Katherine M. Audsley; Alison M. McDonnell; Jason Waithman (Cells, 2020)
The use of dendritic cells (DCs) to generate effective anti-tumor T cell immunity has garnered much attention over the last thirty-plus years. Despite this, limited clinical benefit has been demonstrated thus far. There has been a revival of interest in DC-based treatment strategies following the remarkable patient responses observed with novel checkpoint blockade therapies, due to the potential for synergistic treatment. Cross-presenting DCs are recognized for their ability to prime CD8+ T cell responses to directly induce tumor death. Consequently, they are an attractive target for next-generation DC-based strategies. In this review, we define the universal classification system for cross-presenting DCs, and the vital role of this subset in mediating anti-tumor immunity. Furthermore, we will detail methods of targeting these DCs both ex vivo and in vivo to boost their function and drive effective anti-tumor responses.